Chondroma in the hypoglossal canal: A case report - Arai, Shintaro (Surg Neurol Int, 2019)
BACKGROUND: Intracranial chondromas are rare tumors arising from the skull base. They are usually accompanied by functional impairments of some cranial nerves. However, hypoglossal nerve dysfunction is rare. CASE DESCRIPTION: We report on a 57-year-old woman presenting with chondroma of the right hypoglossal canal leading to right hypoglossal nerve palsy. CONCLUSIONS: This report suggests that chondroma should be considered as a differential diagnosis in cases of hypoglossal lesions.